Indigenous conflict management strategies : global perspectives - Adebayo, A. G. (Akanmu Gafari), 1956-; Benjamin, Jesse J.; Lundy, Brandon D., 1976- (Lexington Books, 2014)
'Indigenous Conflict Management Strategies: Global Perspectives' presents a variety of traditional conflict management approaches as well as several cases of both successful and unsuccessful integrations of Indigenous and Western strategies. As it explores these approaches, this books also analyzes the central characteristics, strengths, and weaknesses of a multitude of Indigenous systems from around the globe.